Comparison of in-hospital outcomes of smoker versus non-smoker patients presenting with acute coronary syndrome - Khan, Abid Ullah; Ahmad, Farooq; Ullah, Qinnat; Khan, Fatima; Nawaz, Muhammad; Ahmad, Zeeshan (International Journal of Pathology, 2026)
Background: Cigarette smoking is a well-established modifiable risk factor for the development of acute coronary syndrome (ACS). However, its impact on short-term, in-hospital outcomes among patients presenting with ACS remains controversial, with conflicting evidence and the ongoing debate surrounding the so-called “smoker’s paradox.” This study aimed to compare in-hospital clinical outcomes between smoker and non-smoker patients presenting with acute coronary syndrome. Methods: This prospective, hospital-based observational comparative study was conducted in the Department of Cardiology, Khyber Teaching Hospital, Peshawar, Pakistan, over a six-month period. Adult patients (≥18 years) presenting with confirmed ACS, including ST-segment elevation myocardial infarction, non–ST-segment elevation myocardial infarction, or unstable angina, were consecutively enrolled. Patients were categorized as smokers or non-smokers based on predefined criteria at admission. Baseline demographic characteristics, cardiovascular risk factors, clinical presentation, and in-hospital management were recorded. In-hospital outcomes, including acute heart failure, cardiogenic shock, arrhythmias, stroke, in-hospital mortality, and length of hospital stay, were compared between the two groups using appropriate statistical tests. Results: A total of 157 patients were included, comprising 85 smokers (54.1%) and 72 non-smokers (45.9%). Baseline characteristics, including age, body mass index, cardiovascular risk factors, ACS type, Killip class, and in-hospital management strategies, were comparable between the two groups. No statistically significant differences were observed between smokers and non-smokers with respect to acute heart failure, cardiogenic shock, arrhythmias, stroke, in-hospital mortality, or length of hospital stay. Conclusion: In this cohort of patients presenting with acute coronary syndrome, smoking status was not associated with differences in short-term, in-hospital clinical outcomes or duration of hospitalization. These findings underscore the importance of distinguishing short-term hospital outcomes from the well-established long-term cardiovascular risks associated with smoking. Despite comparable in-hospital prognosis, smoking cessation remains a critical component of secondary prevention in patients with acute coronary syndrome.